Minimally invasive surgery using posterior-only Pedicle screw fixation in treatment of Adolescent Idiopathic Scoliosis: A Systematic Review and Meta-Analysis. (May 2022) - Fiore, Michele; Ruffilli, Alberto; Viroli, Giovanni; Barile, Francesca; Manzetti, Marco; Faldini, Cesare
Highlights: Only low-quality studies on MIS-PSF in the treatment of AIS are available in the Literature. MIS-PSF seems to be a suitable technique for the treatment of AIS, representing an alternative to open-PSF in selected patients with moderately severe curves and who do not require accessory osteostomies. Compared to open-PSF, MIS-PSF showed lower coronal correction, estimated blood loss and length of hospital stay, but higher operative time. The complication rate of MIS-PSF was similar to that described in the literature using open-PSF. Abstract: Minimally invasive surgery (MIS) techniques for posterior spine pedicle-screw fusion (PSF) may reduce the AIS surgery invasiveness, although they require a certain degree of patient selection based on the severity of the curve. The aim of this article is to systematically review the Literature to determine efficacy and safety of MIS-PSF in AIS correction, and to compare its outcomes with open-PSF. A systematic search of electronic databases from eligible articles was conducted. Only studies adopting MIS-PSF for AIS were included. Clinical and radiographic outcomes were extracted and summarized. Meta-analyses were performed. P-value < 0.05 was considered significant. Thirteen studies for a total of 635 patients ungergoing MIS-PSF were included in this review. Pre-operative Cobb's angle ranged from 48.3°±4.2° to 59.8°±6.6°, coronal correction from 58.1% to 79.1%, average operative time ranged from 252 to 526.8 min, average estimated blood loss from 138.8 ± 50 to 1250 mL. Sixty-seven complications were recorded (9.9%), with 19 revisions (3.8%), resulting similar to those described in Literature using open-PSF. At meta-analysis, MIS-PSF (321 patients) compared to open-PSF (429 patients) showed lower coronal correction (although no statistically significant difference was found), estimated blood loss and length of hospital stay, but higher operative time. No differences in SRS-22, complications and revision rate were found. In conclusion, open-PSF shows a trend towards higher correction in the coronal plane and requires a shorter operative time when compared to MIS-PSF. It remains the gold standard for AIS correction, although MIS-PSF seems to be a viable and promising technique for selected patients. - KEYWORDS: minimally invasive surgery, minimally invasive techniques, adolescent idiopathic scoliosis, posterior spinal fusion, pedicle-screws-only instrumentation.